AWARENESS OF DRUG ABUSE AMONG DENTAL COLLEGE STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Drug abuse has been a serious medical concern worldwide. Given mortality, substance misuse is still liable for serious illness and also the marketing of illegal substances has a significant effect on the community. This study was conducted to determine the awareness of drug abuse amongst dental college students. A cross-sectional survey was done with a self-administered questionnaire comprising of ten questions pertaining to the awareness about drug abuse. The samples chosen for the study were 100 dental undergraduate students. The responses were collected and analysed.82% of the respondents were aware of the dangerous effects of drug abuse .68% said drug abuse is because of stress,8% said because of peer pressure and 20% said because of family problems and 4% said because of pleasure seeking .76 % feel deaddiction therapy can reduce drug abuse . 5% of the respondents have used some kind of drugs .85% said they are aware of health risks associated with drug abuse. There is high level of awareness among dental students regarding the abuse of drugs and associated health risks. However, more intense and wider community outreach programs should be initiated to spread awareness about drug abuse among the general public and the student community